2016
DOI: 10.12669/pjms.322.9266
|View full text |Cite
|
Sign up to set email alerts
|

The eating habits of type 2 diabetics in the region of Ain-Defla (Algeria)

Abstract: Objective:To evaluate the eating habits and the practice of physical-activity of patients with Tyhpe-2 diabetes. (DT2).Methods:A total of 1523 patients DT2 with average age 58±9.9 were recruited. A questionnaire about their eating habits, physical activity was conducted. Data were analyzed using SPSS statistical.Results:Most of the patients were obese (64%), with irregular and weak practice of the physical-activity. The patients based their consumption on food rich with nutrients of high glycaemic index. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…The results of a survey among 1523 Algerians (58.7 ± 9.9 years) using the diet questionnaire suggested the mean energy consumption of 2668 ± 320 kcal; 55% ± 10% of energy was derived from carbohydrates, 13% ± 3% from protein, and 30% ± 7% from fats. The mean intake of dietary fiber was 26 ± 3 g, while in the present study, it was 16.94 ± 5.93 g. In the above study, 64% of subjects were obese compared to 44% in the present study, which may be related to differences in mean energy [10]. In a Jordan study on 198 patients with T2DM (55.9 ± 9.3 years), the mean daily energy consumption was 2279.2 ± 944.4 kcal; 56.7% ± 7.5% of energy was derived from carbohydrates, 15.9% ± 3.1% from protein, and 27.7% ± 6.5% from fat.…”
Section: Discussioncontrasting
confidence: 59%
“…The results of a survey among 1523 Algerians (58.7 ± 9.9 years) using the diet questionnaire suggested the mean energy consumption of 2668 ± 320 kcal; 55% ± 10% of energy was derived from carbohydrates, 13% ± 3% from protein, and 30% ± 7% from fats. The mean intake of dietary fiber was 26 ± 3 g, while in the present study, it was 16.94 ± 5.93 g. In the above study, 64% of subjects were obese compared to 44% in the present study, which may be related to differences in mean energy [10]. In a Jordan study on 198 patients with T2DM (55.9 ± 9.3 years), the mean daily energy consumption was 2279.2 ± 944.4 kcal; 56.7% ± 7.5% of energy was derived from carbohydrates, 15.9% ± 3.1% from protein, and 27.7% ± 6.5% from fat.…”
Section: Discussioncontrasting
confidence: 59%
“…Further research related to quality of life and healthy lifestyles of PWD for both adults and children may apply this tool to measure or identify the emotional distress among PWD and to recommend appropriate treatment programs, including healthy diet and regular physical activity. 28,29 Furthermore, clinicians could collect valid data of emotional distress within two minutes to assist them in treating the health problems in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies have shown that those with poor mental health are at higher risk of worse oral health, including dental caries [37]. Second, literature suggests that those with diabetes in general tend to have poor eating habits [38,39]. In turn, poor eating habits are associated with worse oral health [40].…”
Section: Discussionmentioning
confidence: 99%